Silver recovery from spent IPA using solid liquid extraction - Khairul Afif, Mohammad (2012)
Perhaps the most challenging field in environmental engineering practice at the present time is the treatment and disposal of industrial and hazardous wastes.Isopropyl alcohol (IPA) is an organic solvent that widely use as a cleaning agent in electronic industry,particularly for solder paste cleaning of defective electronic products.The spent IPA consist of solder paste can cause a serious problem in term of storage and pollution since it contains high concentration of heavy metals.There are few possible alternatives to treat this waste and one of the ways is to recover precious metal such as silver.In this study,a sample of waste IPA is taken from one electronic company in Pahang which consume almost 100kg of IPA every three weeks. This company use IPA as a cleaning agent.Solid-liquid extraction (leaching process) is used in this study to extract the silver because of its simplicity,environmental friendly, lower cost and provides high purity of product.In order to get better understanding in this study,few parameters such as type of leaching agent,concentration of leaching agent and retention time were investigated.Based on the result obtain, it can conclude that all the parameters affect silver leaching.Most of leaching agent that been used in this study show the potential on silver leaching because of the existence of free chloride ions produce by HCl and form silver chloro complexes with Ag+ ions. The percentage of silver leaching also high which is up to 90% due to the effect of leaching agent concentration.This study is believed to be the first attempt to extract silver from spent IPA.